Analisis Pengaruh Tingkat Kecanduan Media Sosial terhadap Kualitas Tidur Mahasiswa Psikologi Universitas Jambi - Anggi Maretha Wulandari; Ariqah Akbari; Nur Aufa Hermasyawilla; Beny Rahim; Muhammad Ilham; Jelpa Periantalo (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
This study aims to identify the relationship between Social Media Addiction and Sleep Quality of Jambi University Psychology Students. This study uses quantitative research with a correlational test approach. The sampling technique was random sampling with the study population consisting of 88 Jambi University Psychology students class of 2024. Data collection was carried out through questionnaires distributed to 88 students of the Jambi University Psychology Department. Data analysis includes two approaches: (1) descriptive analysis, 2) normality testing, 3) validity and reliability testing, and 4) hypothesis testing using Spearman's rho correlation. Based on the results of the analysis in this study, it shows that there is no relationship between Social Media Addiction and Sleep Quality of Psychology Students of Jambi University (UNJA). This is evidenced by the p value having a value of 0.402. The p value has a value greater than 0.05 so that the Working Hypothesis (H1) is rejected and the Null Hypothesis (H0) is accepted.